Organophosphorus and organochlorines: medical toxicology and environmental reflexes (Research, Society and Development, 2021)
Pesticides or agrochemicals are chemical substances used in agriculture, because they have activity on countless living organisms that are harmful to crops. In this context, the organophosphorus and organochlorine compounds are of great relevance, due to the human intoxication of medical importance and environmental contamination. The objective of this work is to systematize information, contextualizing the problem in a critical way with emphasis on ecotoxicology and it’s medical consequences, associated with the use of organophosphorus and organochlorine compounds. To this end, a narrative literature review was conducted, outlined by searching for scientific articles and bibliographies about such compounds in the main international electronic repositories. The descriptors used for the search were: pesticides, agrochemicals, organochlorines, organophosphorus, toxicity, diagnosis, treatment, and environmental impact. Diagnosis is mostly clinical, but laboratory tests for evaluation/diagnosis can be performed, such as determination of erythrocyte cholinesterase (AChE) activity and plasma cholinesterase (BChE), for prognostic/monitoring purposes in chronic cases. Other tests may also be requested for analysis and investigation. The therapeutic protocol in cases of organophosphate intoxication consists of the administration of drugs with antagonistic activity to the substances, such as atropine and oximes, activated charcoal, anticonvulsant/neuroprotective drugs, and intensive care when necessary. However, there is no definitive treatment for organochlorine toxicity. Despite their high toxicity to the environment and to life forms, organophosphate compounds continue to be used for agricultural pest control, while organochlorines are used for vector control/disease dissemination. Moreover, such compounds are associated with occupational accidents and suicide.